Creative accounting: main causes that motivate its use in companies of the San Francisco Municipality of Zulia State in Venezuela (Revista Científica Compendium, 2021)
The objective of the research was to analyze the main causes that motivated the use of creative accounting in companies of the San Francisco Municipality of the Zulia State in Venezuela. It was a descriptive field study, with a sample of 15 companies in the area, selected based on social capital, operating time and the sector to which they belong. A survey as data collection technique was used. It was validated by the assessment of three (3) experts in the area. It was concluded that managers and accounting professionals manipulate the figures to reflect a favorable reality of the organizations. This practice is used by senior management as a strategic management tool; it is framed in the legality of the use of gaps in accounting standards. However, manipulating the numbers represents fraud, which runs against the goal of financial accounting and the ethics of the accounting professional.
Keywords: Creative accounting; accounting manipulation; International Accounting Standards (IAS); International Financial Reporting Standards (IFRS)